Evaluation of intestinal tissue safety during the compression process of circular end-to-end anastomosis stapler based on finite element simulation - Zhou, Yuanda; Tan, Zhen; Jiang, Peishi; Sun, Yi; Wu, Dewang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveCurrently, there is no standardized finite element analysis method for investigating the safe compression range of circular end-to-end anastomosis stapler. This study aims to develop a finite element analysis framework based on stress thresholds and the volumetric distribution of tissue states, and to investigate the effects of tissue thickness and compression ratio on the risk of compression-induced injury during anastomosis. The evaluation is conducted by calculating the proportion of the volume of elements categorized as “effective fixation” or “damaged” based on equivalent stress.MethodsA disposable circular end-to-end anastomosis stapler was used as the reference model to create a 1:1 scale 3D model of the key components at the contact surface, including the anvil, staple cartridge, and cutting washer. Finite element models of intestinal tissue with varying thicknesses were established within the environment of the circular stapler. Different compression ratios were applied to analyze the stress distribution in the intestinal tissue.ResultsAcross experiments with intestinal tissues of all thicknesses, the safe compression ratio consistently centered around 60%. The maximum equivalent stress on the lower intestinal segment was always greater than that on the upper segment, while the average equivalent stress of the upper and lower intestinal segments exhibited a collinear distribution across experiments with varying tissue thickness. An increase in total tissue thickness positively contributed to the expansion of the safe compression range. In asymmetric tissue thickness models, the side with greater thickness demonstrated a broader safe compression range.ConclusionThe safe compression range of staplers is closely related to the properties and thickness of the tissue. This study provides a framework for simulating and determining the safe compression range of staplers.